Association between Survival Time and Changes in NT‐proBNP in Cats Treated for Congestive Heart Failure. (31st March 2017) - Pierce, K.V.; Rush, J.E.; Freeman, L.M.; Cunningham, S.M.; Yang, V.K.
Abstract : Background: Reductions in N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP) concentrations after treatment have been associated with improved survival in people with congestive heart failure (CHF), but have not been reported in cats with CHF. Objectives: To evaluate changes in NT‐proBNP concentrations in cats with CHF after treatment and determine whether serial NT‐proBNP measurements provide prognostic information. Animals: Thirty‐one client‐owned cats. Methods: Prospective, observational study in cats with new onset CHF secondary to cardiomyopathy. Concentrations of NT‐proBNP were measured within 4 hours of admission to the hospital, on the day of discharge, and at re‐evaluation 7–10 days later. Results: Median NT‐proBNP concentrations decreased significantly from admission (1, 713 pmol/L [range, 160–3, 784 pmol/L]) to discharge (902 pmol/L [range, 147–3, 223 pmol/L]); P = .005) and from admission to re‐evaluation (1, 124 pmol/L [range, 111–2, 727 pmol/L]; P = .024). Median survival time was 109 days (range, 1–709 days), with 5 cats still alive at the time of analysis. Cats with a larger percent decrease in NT‐proBNP from admission to discharge had a longer survival time ( P = .048). Cats with evidence of active CHF at the time of re‐evaluation ( P = .010) and cats whose owners had difficulty administering medications ( P = .045) had shorter survival times. Conclusions and clinical importance: Cats with a larger percent decrease in NT‐proBNP during hospitalization and no evidence of CHF at the time of re‐evaluation had longer survival times. Additional studies are needed to determine whether NT‐proBNP can help guide treatment in cats with CHF.